(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2022)
This study aims to measure students’ vocabulary by analyzing the acquisition of test results before and after the implementation of the treatment in the form of a vocabulary test in class. The study population was class VIII MTS Al-Hikmah Parombean students in the 2022/2023 academic year. The main question is to find out how the students’ vocabulary mastery in learning English. The technique used to obtain data is to collect data from students’ vocabulary tests; count and classify vocabulary mastery tests; and draw conclusions based on the data results. The results showed that there was an increase in students’ vocabulary mastery it can be seen that the student’s vocabulary scores on the pre-test were not good at 54.03 with a standard deviation of 11.895 then the minimum score was 33 and the maximum score was 73, and increased in the post-test average of 75.60 with a standard deviation is 8,873 then the minimum score is 60 and the maximum score is 87. The researcher calculated the average score of the student’s vocabulary mastery test using descriptive statistics spss v26. It can be concluded that the students’ vocabulary mastery at MTS Al-Hikmah Parombean after being given treatment improved well, meaning that students were able to capture the material, accept and apply the material described by the researcher